SOME PROPERTIES OF MODULAR TOPOLOGY IN THE ORLICZ SEQUENCE SPACE - Haryadi Haryadi; Solikhin Solikhin (Journal of Fundamental Mathematics and Applications (JFMA), 2025)
In this article, we examined some properties of modular topology on the Orlicz sequence space. Discussions were conducted by constructing the topology on the sequence space using a modular neighborhood of zero. The neighborhood forms a local base that is balanced, absorbing, and symmetrical. Furthermore, if the Orlicz function that grows not soo rapidly, the modular neighborhood induces a topological vector space. We also characterize the modular boundedness, modular convergence, and modular closed set on the sequence space.